Optimalisasi Sumber Pendapatan Publik Islam Melalui Model Islamic Circular Fiscal System (ICFS): Perspektif Keuangan Berkelanjutan - Saparuddin Saparuddin; Muhammad Hasanuddin (Studia Economica : Jurnal Ekonomi Islam, 2025)
This study develops the Islamic Circular Fiscal System (ICFS) as a conceptual model for optimizing Islamic public revenue sources in a sustainable manner. Using a qualitative-descriptive approach based on library research, this study integrates the principles of maqasid al-shariʿah, circular economy theory, and Islamic fiscal policy literature to formulate circular mechanisms in the management of zakat, infaq, and waqf. The results of the study introduce two main frameworks: the Circular Fiscal Governance Framework (CFGF), which functions as a model for institutional governance and coordination between Islamic fiscal institutions, and the Circular Fiscal Performance Index (CFPI), which is proposed as an evaluative instrument for circular fiscal effectiveness. Through the ICFS approach, this study emphasizes the importance of integrating sharia values with economic sustainability principles in forming a productive, fair, and transparent Islamic fiscal system. The study also highlights the role of digital governance, public-private partnerships, and the strengthening of Islamic financial instruments (such as waqf sukuk) as prerequisites for ICFS implementation. Due to its conceptual nature, this study recommends empirical testing of the effectiveness of CFGF and CFPI in the practice of Islamic fiscal policy in the future